Disability, Mortality and Causes of Death in a 19th-Century Swedish Population - Vikström, Lotta; Edvinsson, Sören; Häggström Lundevaller, Erling (Historical Life Course Studies, 2021)
Our study aims to find how disability affected human health in historical time through an examination of individuals' mortality risks and death causes. Swedish parish registers digitized by the Demographic Data Base (DDB) enable us to account for a relatively high number of persons reported to have disabilities, and to compare them with a group of non-disabled cases. The findings concern a 19th-century population of 35,610 individuals in the Sundsvall region, Sweden, and show that disability increased the premature mortality risk substantially. Disability seems to have jeopardized men’s survival in particular, and perhaps due to gendered expectations concerning the type of work men and women became less able to perform when disabled. Our study of death causes indicates that their deaths were less characterized by infectious diseases than among the non-disabled group, as a possible consequence of lower exposure to infections due to the way in which disability could impede opportunities for interaction with peers in the community. In all, our mortality findings suggest that disability was associated with poor living conditions and limited possibilities to participate in work and social life, which further tend to have accumulated across life and resulted in ill health indicated by premature death.